HUBUNGAN ANTARA MINAT MENJADI GURU SEKOLAH DASAR DENGAN KESIAPAN MENGAJAR MAHASISWA CALON GURU SEKOLAH DASAR - Haqqi, Ulyani Lizamil; Witri, Gustimal; Suroyo, Suroyo; Ibrahim, Bedriati; Hermita, Neni (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
This study aims to find out the relationship between the interest in becoming an elementary school teacher and the teaching readiness of PGSD FKIP UNRI students. This study uses a quantitative approach with a survey method. This research was conducted at PGSD FKIP UNRI which involved 118 active students of PGSD FKIP UNRI class of 2018. The data collection technique in this study used a questionnaire with a sampling technique, namely total sampling. Total sampling is a sampling technique in which all members of the population are sampled in order to obtain representative research results. The validity test of the questionnaire used the product moment correlation technique, while the reliability test used the Alpha Cronbach formula. As for the prerequisite analysis test, the normality test and linearity test were carried out. Then do the hypothesis testing with the product moment correlation test. The level of significance of the analysis results was set at 5%. This data analysis technique was carried out with the help of the SPSS version 21 program. The results in this study can be concluded that there is a positive and significant relationship between interest in being an elementary school teacher and Teaching Readiness of PGSD FKIP UNRI students class of 2018 which is shown by the results of the correlation coefficient r count (0,506) > r table (0,180).